2009
DOI: 10.1007/s10152-009-0161-z
|View full text |Cite
|
Sign up to set email alerts
|

Brooding in Psolus patagonicus (Echinodermata: Holothuroidea) from Argentina, SW Atlantic Ocean

Abstract: The mode, season, and time of brooding, egg diameter, egg number per brood, and the characteristics of newly released juveniles of Psolus patagonicus were investigated oV Mar del Plata, Buenos Aires, Argentina, between October 1999 and February 2001. Individuals were attached to the Patagonian scallop, Zygochlamys patagonica. Spawning occurs between February and March. The mean egg diameter, 887 § 26 m, is the highest reported for the family Psolidae. Eggs are brooded under the mother's sole until they develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Some lecithotrophic holothurians reproduce by brooding of the embryos on the body of the adults, a reproduction strategy that has been observed in numerous species [ 74 , 139 ]. Examples are the cucumariid holothuroid Neocnus incubans [ 4 ], the deep-sea Holothurian Oneirophanta mutabilis [ 63 ], and the Atlantic Ocean Psolus patagonicus [ 58 ]. The great variety of reproductive strategies in holothurians is highlighted by the recent discovery that brooding in Holothuria floridana is facultative since the exceptionally sticky embryos can benefit from growing on the adult body wall but can also live in the plankton [ 132 ].…”
Section: Embryonic Development and Metamorphosismentioning
confidence: 99%
“…Some lecithotrophic holothurians reproduce by brooding of the embryos on the body of the adults, a reproduction strategy that has been observed in numerous species [ 74 , 139 ]. Examples are the cucumariid holothuroid Neocnus incubans [ 4 ], the deep-sea Holothurian Oneirophanta mutabilis [ 63 ], and the Atlantic Ocean Psolus patagonicus [ 58 ]. The great variety of reproductive strategies in holothurians is highlighted by the recent discovery that brooding in Holothuria floridana is facultative since the exceptionally sticky embryos can benefit from growing on the adult body wall but can also live in the plankton [ 132 ].…”
Section: Embryonic Development and Metamorphosismentioning
confidence: 99%
“…plates) on the surface of the body wall, common to all members of the Psolidae family, that measure between 450 mm in diameter in 3-month-old juveniles and 1.4 cm in the largest adults, making them easier to distinguish. While investigators had reported the presence of these plates in psolid species before [39][40][41][42], their porous aspect and uniform colour probably prevented them from being considered potential indicators of age. Moreover, these plates can be challenging to extract without damaging their fine structure.…”
Section: Discussionmentioning
confidence: 99%
“…Psolus patagonicus was reported as a brooder by Bernasconi (1941), Hernández (1981) and Giménez & Penchaszadeh (2010). Martínez et al (2011) studied the reproductive cycle and found a spawning event during February, which is followed by a brooding period from February to September (Giménez & Penchaszadeh 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In the Pacific Ocean, known from the vicinity of Magellan Strait (48° S) (Hernández, 1981). Habitat: Rocks, shells, Macrocystis fronds and holdfast (Pawson, 1969a;Giménez & Penchaszadeh 2010, and this paper).…”
mentioning
confidence: 97%